The Enhancing Women's Contraceptive Decision-Making: A Qualitative Study of IUD Adoption Among Women of Childbearing Age - Yani, Ahmad; Sudirman, Sudirman; Afni, Nur; Syukran, Muhammad (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Family Planning (KB) initiatives seek to manage population growth by curbing childbirths among women aged 15-49. This qualitative research investigates the decision-making process of women of childbearing age (WUS) when choosing intrauterine device (IUD) contraception in Batuoge Village, Pedongga District, Pasangkayu Regency. Employing observation, in-depth interviews, and documentation, the study reveals that WUS possess limited knowledge of IUD contraception, primarily at the basic level. Furthermore, their attitude toward IUD contraception tends to be less favorable. In terms of action, WUS generally engage in consultations with their partners. This research highlights the need for improved knowledge and attitudes regarding family planning (KB) with intrauterine device (IUD) contraception among women of childbearing age in Batuoge Village. It emphasizes their inclination toward consultation with their partners.